2022
DOI: 10.2460/javma.22.01.0033
|View full text |Cite
|
Sign up to set email alerts
|

Medical futility is commonly encountered in small animal clinical practice

Abstract: OBJECTIVE To document veterinarians’ perceptions and understanding of medical futility and determine the frequency with which medical futility occurs in small animal practice. SAMPLE 477 veterinarians in small animal general and specialty veterinary practice. PROCEDURES A cross-sectional study was performed with a 25-question, web-based, confidential, anonymous survey distributed through various professional veterinary specialty associations. RESULTS Nearly all respondents (469/474 [99.0%]) believed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…From the perspective of animal hospice, a palliated natural death, if requested by the animal patient's owner, is acceptable as long as the animal is comfortable and not in pain ( 23 ). There have been only a few attempts made at approaching veterinarians' perspectives concerning animal hospice and care perceived as medically futile or non-beneficial, for example ( 31 , 32 ). Small animal practitioners in the US commonly encounter requests for what veterinarians deem as futile care but also agree that there are situations where its provision is appropriate ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From the perspective of animal hospice, a palliated natural death, if requested by the animal patient's owner, is acceptable as long as the animal is comfortable and not in pain ( 23 ). There have been only a few attempts made at approaching veterinarians' perspectives concerning animal hospice and care perceived as medically futile or non-beneficial, for example ( 31 , 32 ). Small animal practitioners in the US commonly encounter requests for what veterinarians deem as futile care but also agree that there are situations where its provision is appropriate ( 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…There have been only a few attempts made at approaching veterinarians' perspectives concerning animal hospice and care perceived as medically futile or non-beneficial, for example ( 31 , 32 ). Small animal practitioners in the US commonly encounter requests for what veterinarians deem as futile care but also agree that there are situations where its provision is appropriate ( 31 ). However, veterinarians disagree on whether palliative sedation is appropriate EOL care ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…1 Of the veterinarians who participated in a 2022 cross-sectional study, 30% disagreed that 'all treatment options should be presented to owners'. 19 Which options are introduced by veterinarians to clients and how information is presented influence the direction of the consultation. 14 The emergence of communication as a key influencer in the consultation room…”
Section: Introductionmentioning
confidence: 99%
“…1 The authors identified the need for similar interventions in veterinary medicine, where futility of care and moral stressors are commonly encountered in the course of practice. 2,3 Indeed, a recent review of literature examining veterinary well-being found a high prevalence of psychological stressors and increased risk of burnout, anxiety and depressive disorder in veterinarians compared to other occupational groups. 4 Significant psychological distress was found among the veterinary workforce by the Merck Veterinary Wellbeing Study III, 5 with 9.4% of veterinarians experiencing serious psychological distress, a steady increase from prior reports in 2017 and 2019.…”
Section: Introductionmentioning
confidence: 99%